THE EFFECT OF TRAINING AND EMPLOYEE MOTIVATION ON EMPLOYEE PRODUCTIVITY: A LITERATURE REVIEW - Dalimunthe, Ritha F.; Hajar , Siti; Pardede , Safira Nadila; Sirait , Bertiana; Ivana, Nahda (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the effect of training and employee motivation on employee productivity. The method used in writing this article is with qualitative methods and literature review (Library Research). Research results The literature review shows that training and work motivation have a positive influence on employee work productivity. Proper training can improve employees' skills and knowledge, allowing them to work more efficiently and effectively. High employee motivation can also increase productivity as motivated employees tend to be more passionate and dedicated in completing their tasks. The studies conducted show that training and motivation have a positive influence on employee work productivity, both individually and simultaneously. Company policies that support employee skill development and create a motivating work environment can yield long-term benefits in the form of increased productivity, performance and job satisfaction.